Awareness about sexually transmitted diseases in women related to their age, education and income - Hafeez, Tayyaba; Ahmed, Yashfeen; Ahmad, Maria (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the level of awareness about sexually transmitted diseases in females coming from different age groups and to investigate the role that education and social status may play on their knowledge. Methods: Study design: Cross Sectional Setting: CMH Lahore Gynaecology Out Patient Department Time frame: June 2019 till July 2019. Sample size: 337 Inclusion criteria: Patients included in this study presented to the CMH Gynaecology OPD during June to July 2019 and gave an informed consent about participation in the research. Exclusion criteria: Anyone who did not give consent. Data collection: Patients were given a hard copy of the questionnaire to fill. Any queries were answered on the spot. Data Analysis: SPSS version 23. Results: Of the 337 patients interviewed, 158 were aged 26-35 years. 71 patients were undergraduates and 99 had completed post graduate studies. 205 patients belonged to families with an income of less than RS.50, 000. 229 females had presented for a routine pregnancy checkup. 244 of the 337 patients had attested to know about STD’s. The most common source of their knowledge was through TV (142), followed by the internet (137). 251 of the 337 patients were familiar with limited STDs such as AIDS and Hepatitis B. Conclusion: Age, level of education and income had a profound effect on the knowledge regarding Sexually transmitted diseases amongst the women in Pakistan. Keywords: Sexually transmitted diseases, sexual and reproductive health, STD’s, STI’s, venereal diseases.